Fatwa Authority of the Indonesian Ulema Council on the Formation of Religious Regulations in Indonesia: Siyāsah Dusturiyah Perspective - Aswan; Ashufah, Abdul Hayyaqdhan (MUI Sulawesi Selatan, 2023)
This study aims to determine the urgency of MUI fatwas in people's lives and the position of MUI fatwas in the formation of government policies in Indonesia as well as to analyze the formation of government policies on the influence of MUI fatwas studied in Siyasah Dusturiyah's view. The problem in this study is the authority of MUI fatwas in influencing legal politics in Indonesia while the procedure for forming MUI fatwas is not regulated in Law Number 12 of 2011 concerning the Establishment of Laws and Regulations. This research is a library research with a syar'i normative theological approach. Primary and secondary data sources such as: UUD, MUI Fatwa, al-Qur'an, hadith, scientific journals. The results of this study are 1) The urgency of MUI fatwas in people's lives as a guide in finding solutions related to problems using a systematic methodology based on strong propositions for the benefit of the general public, especially Muslims. 2) MUI's fatwa in its position on policy formation is an infra-structural element in the group of institutional interest groups (Institutional Interest Group). 3) MUI fatwas are regulations and laws required by the state in terms of conformity with religious principles and are the realization of community benefit. So that the MUI fatwa is present to assist the government in solving a problem in society, especially Muslims called the ifta institution.